2005
DOI: 10.1021/nl048192+
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Concentric Quantum Double Rings

Abstract: We demonstrate the self-assembled formation of concentric quantum double rings with high uniformity and excellent rotational symmetry using the droplet epitaxy technique. Varying the growth process conditions can control each ring's size. Photoluminescence spectra emitted from an individual quantum ring complex show peculiar quantized levels that are specified by the carriers' orbital trajectories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
381
1
10

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 385 publications
(407 citation statements)
references
References 22 publications
15
381
1
10
Order By: Relevance
“…7(b)] [23,52]. In between these two extremes, more complex morphologies, such as double rings and molecules, can be obtained [30,35,37,40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7(b)] [23,52]. In between these two extremes, more complex morphologies, such as double rings and molecules, can be obtained [30,35,37,40].…”
Section: Discussionmentioning
confidence: 99%
“…The As pressure and substrate temperature during crystallization are used to control nanostructure morphology [30,35,37,40]. Three sets of samples (P , T , and V ) were grown in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent progress in nanofabrication technology allows the simulation of novel atomic physical phenomena on an artificial platform, such as presence of ÎŽ-function-like density of states on quantum dots (QD) 1,2 , realization of molecularorbital state on spatially coupled QDs 3,4 , and formation of nanometer-sized quantum rings 5,6,7,8 , which are nanoscopic analogues of benzene. Among them, fabrication of semiconductor quantum rings has triggered strong interest in realization of quantum topological phenomena, which are expected in a small systems with simply-connected geometry 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…From the experimental point of view, much effort has been devoted in the past decade to the fabrication of GaAs/AlGaAs concentric double quantum rings using droplet-epitaxial techniques [15][16][17] in order to study the Aharonov-Bohm effect [18] and the influence of the Coulomb interaction on the magnetic properties [17]. More recently, accurate theoretical calculations, using local spin density functional theory [19], exact diagonalization [20] and quantum Monte Carlo [21] techniques, have shown that Wigner molecules [22] are formed at low density.…”
Section: Introductionmentioning
confidence: 99%